First occurrence of Quadrigyrus nickoli (Acanthocephala) in the ornamental fish Hyphessobrycon eques - FUJIMOTO, Rodrigo Yudi (2015)
The objective of this work was to report the first seasonal occurrence of the acanthocephalan Quadrigyrus nickoli Schmidt & Hugghins, 1973 (Quadrigyridae), in the “Mato Grosso” Hyphessobrycon eques (Characidae) (Steindachner, 1882), collected from the Chumucuí River, state of Pará, Brazil. The fish were collected between July 2006 (rainy season) and June 2007 (dry season) and were examined for parasites using pattern techniques. A total of 75 parasites were found in the stomach and intestine. Among 83 fish examined (50 in the dry season and 33 in the rainy season), 22 were parasitized by cystacanths of Q. nickoli. The importance of H. eques as a paratenic host for Q. nickoli is discussed. This is the first study on the biology of and infection by Q. nickoli occurring in the eastern Amazon region.